Determinasi Literasi Keuangan dan Inklusi Keuangan Terhadap Kinerja dan Keberlangsungan Usaha UMKM - Bunga Permata Sari; Dheo Rimbano; Beny Marselino; Chici Aprilia Sandy; Resti Ria Hairum (Owner : Riset dan Jurnal Akuntansi, 2022)
This article is the result of a review to see how the determination of Financial Literacy and Financial Inclusion on MSME Business Performance and Sustainability. Based on the results of previous related research. The results of the review using the Systematic Literature Review (SLR) from studies contained in journals published on https://scholar.google.com range from 2016 – 2021. Where the results state that: Financial Literacy affects MSME Performance, Inclusion Finance has an effect on MSME Performance, Financial Literacy has an effect on MSME Business Continuity, Financial Inclusion has no effect on MSME Business Continuity, and Financial Literacy has an effect on MSME Financial Inclusion